2021
DOI: 10.1166/jnn.2021.18689
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Targeted Poly(lactic-co-glycolic acid) Nano-Delivery Carriers in the Treatment of Hemangiomas

Abstract: Hemangiomas, also called infantile hemangiomas (IH), are the most common congenital benign vascular tumors in infants and young children. At present, there are many treatment methods for proliferative hemangiomas, which have different effects and lack predictability. Propranolol has gradually replaced glucocorticoids as the first-line treatment for infants and young children with hemangiomas. However, premature discontinuation is prone to relapse, and the efficacy and safety of medication need to be further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They can also prevent enzyme-induced degradation to enhance the clinical efficacy of drugs, improve drug permeability to vascular tumors, and prolong the retention time of drugs in the tumor. 42 In recent years, there have been increasing reports on the use of nucleic acid drugs for gene therapy in tumors. 57,58 However, nucleic acids need to enter cells to exert their therapeutic effects, and cell entry is challenging because nucleic acids are prone to degradation by nucleases during the delivery process, making it difficult to maintain a stable and intact structure before entering cells.…”
Section: Increasing the Stability Of Drugs And Reducing The Immunogen...mentioning
confidence: 99%
See 3 more Smart Citations
“…They can also prevent enzyme-induced degradation to enhance the clinical efficacy of drugs, improve drug permeability to vascular tumors, and prolong the retention time of drugs in the tumor. 42 In recent years, there have been increasing reports on the use of nucleic acid drugs for gene therapy in tumors. 57,58 However, nucleic acids need to enter cells to exert their therapeutic effects, and cell entry is challenging because nucleic acids are prone to degradation by nucleases during the delivery process, making it difficult to maintain a stable and intact structure before entering cells.…”
Section: Increasing the Stability Of Drugs And Reducing The Immunogen...mentioning
confidence: 99%
“…In addition, the experiment showed that the mechanism of PLGA-PP in the treatment of hemangioma involves the downregulation of the Id-1 gene, thereby inhibiting the colonization of HemECs and promoting its apoptosis effect. 42 To improve the transdermal delivery of propranolol hydrochloride (PRH), researchers loaded PRH into cubic liquid crystal nanoparticles (PRH-CNPs) with a cubic structure similar to the cell membrane. Compared to the PRH solution, PRH-CNPs showed significantly increased skin permeability and higher cytotoxicity against mouse hemangioendothelioma (EOMA) cells.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations